Novel PEEK (Polyether Ether Ketone) material for preparing fan frame body and preparation process of PEEK material
By adding polytetrafluoroethylene, compatible agent, antioxidant, carbon fiber and modified glass fiber to PEEK materials, and adopting melt extrusion process, the problem of poor strength in thermal processing is solved, and the fan is realized The frame has high strength, wear resistance and long life.
Patent Information
- Application Number
- CN202411393578.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-02-07
AI Technical Summary
PEEK materials are prone to form ambiguous crystals during thermal processing, resulting in internal stress accumulation and affecting the overall strength.
A new fan frame is used to prepare a formula for PEEK material, including PEEK, polytetrafluoroethylene, compatibility agents, antioxidants, carbon fibers and modified glass fibers, and is prepared by melt extrusion process.
It realizes the lightweight, high strength and good wear resistance of PEEK materials, can withstand vibration and impact during fan operation, and extends the service life of the fan frame.
Smart Images

Figure BDA0005073109380000091 
Figure BDA0005073109380000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of PEEK materials, and more specifically, to a novel PEEK material for fan frame system and a preparation process thereof. Background Art
[0002] PEEK (polyetheretherketone) is a high-performance thermoplastic polymer belonging to the polyetherketone family. Known for its excellent mechanical properties, chemical stability and thermal stability, it is widely used in aerospace, automotive, medical, electronics and oil and gas industries.
[0003] Many power devices are used in aircraft to provide power modules with different voltages. The power supply will emit a lot of heat during operation, which needs to be dissipated. A common practice is to set up a small cooling fan for heat dissipation. The frame of the cooling fan has high requirements on materials. PEEK material is usually used, which has excellent high temperature resistance, good self-lubrication and good corrosion resistance. However, during the heat treatment process of PEEK material, amorphous crystals are easily formed inside, resulting in internal stress accumulation, resulting in local stress concentration and affecting the overall strength. Summary of the invention
[0004] In order to improve the problem of poor strength of PEEK materials during thermal processing, the present application provides a novel PEEK material for fan frame system and a preparation process thereof.
[0005] In the first aspect, the present application provides a novel PEEK material for a fan frame system, which adopts the following technical solution: A novel PEEK material for fan frame system comprises the following raw materials by weight: 55-60 parts of PEEK, 9-12 parts of polytetrafluoroethylene, 2-5 parts of compatibilizer, 1-2 parts of antioxidant, 15-20 parts of carbon fiber and 7-10 parts of modified glass fiber.
[0006] By adopting the above technical solution, the density of PEEK is low, and the new fan frame is lightweight. PEEK has high strength, high rigidity and good wear resistance, and can withstand the vibration and impact generated when the fan is running, maintain the structural stability and integrity of the frame, and help improve the reliability and safety of the fan; PEEK also has excellent chemical resistance and high temperature resistance, can resist the erosion of corrosive substances, and extend the service life of the fan frame. Polytetrafluoroethylene has an extremely low friction coefficient and excellent self-lubricating properties, which can enhance the sliding properties of PEEK, reduce friction and wear, and reduce friction and wear between moving parts inside the fan frame. In addition, polytetrafluoroethylene has extremely strong chemical corrosion resistance, good high temperature resistance and weather resistance, thereby improving the corresponding performance of PEEK materials.
[0007] Compatibilizer improves the interfacial compatibility between PEEK and polytetrafluoroethylene, reduces the interfacial tension between PEEK and PTFE, promotes the uniform dispersion of the two, forms a more stable mixed system, and improves the mechanical strength, toughness, impact resistance and wear resistance of PEEK, making it perform better when subjected to external forces. The role of antioxidants in fan frames is mainly reflected in protecting materials from oxidative degradation and extending the service life of fan frames. Carbon fiber has good corrosion resistance, good thermal stability, extremely high tensile strength and rigidity, is light in weight, and can withstand the high wind pressure and dynamic loads generated when the fan is running, making the fan frame high in strength. In combination with PEEK, it improves the mechanical properties of PEEK materials such as tensile strength, compressive strength and rigidity. In addition, the hardness and wear resistance of carbon fiber make PEEK materials perform well in friction and wear environments, extending the service life of the material.
[0008] The modified glass fiber has high tensile strength, corrosion resistance and low density, which enables the fan to withstand dynamic loads during operation and ensure the stability and safety of the frame structure. It is combined with PEEK and carbon fiber to improve the wear resistance, tensile strength, compressive strength and corrosion resistance of the PEEK material. Various raw materials cooperate with each other to jointly improve the mechanical strength and wear resistance of the PEEK material. It will be subsequently used in the new fan frame to improve the durability of the new fan frame and extend the service life of the new fan frame.
[0009] Optionally, the carbon fiber is pretreated, comprising the following steps: (1) dispersing the carbon fiber in hydrogen peroxide, stirring for 15-20 minutes, washing with water, and then dispersing in concentrated nitric acid, stirring for 0.5-1 hour at a temperature of 66-70° C., filtering, and washing to obtain surface-treated carbon fiber; (2) dispersing the hollow glass microspheres in concentrated sulfuric acid, stirring for 20-25 min, washing with water, and then dispersing in an aqueous solution of a silane coupling agent, stirring for 1-2 h, and filtering to obtain pretreated hollow glass microspheres; (3) Dispersing the surface-treated carbon fiber of step (1) in deionized water, adding the pretreated hollow glass microbeads and nano-silver particles of step (2), stirring for 2-3 hours, and filtering to obtain pretreated carbon fiber.
[0010] By adopting the above technical solution, the surface of carbon fiber is stripped with hydrogen peroxide, which not only removes organic pollutants and residues, but also improves the interfacial bonding between carbon fiber and matrix material, which is helpful for the subsequent mixing of carbon fiber with other materials. Nitric acid further oxidizes the surface of carbon fiber, introduces polar functional groups such as carboxyl and hydroxyl, improves the surface activity of carbon fiber, and enhances its interfacial bonding with polymer matrix, thereby improving the performance of carbon fiber composite materials.
[0011] Concentrated sulfuric acid corrodes the surface of the hollow glass microspheres, making the surface of the hollow glass microspheres uneven and rough, thereby increasing the specific surface area of the hollow glass microspheres. The hollow glass microspheres are then mixed with a silane coupling agent, which chemically adsorbs or chemically bonds with the silanol groups on the surface of the hollow glass microspheres through the reactive groups in its molecular structure to form siloxane bridges, thereby improving the dispersibility of the hollow glass microspheres in the polymer matrix and avoiding agglomeration.
[0012] Carbon fibers, hollow glass microspheres and nano-silver particles are mixed. Hollow glass microspheres have the characteristics of light weight, high strength, insulation and heat resistance, while carbon fibers have the characteristics of high strength, high modulus and low density. Hollow glass microspheres can be loaded on the surface and pores of carbon fibers, increasing the strength, toughness and wear resistance of carbon fibers. Nano-silver particles have excellent antibacterial properties, improving the antibacterial and strength and other mechanical properties of PEEK. Nano-silver particles can be loaded in the pores of carbon fibers and hollow glass microspheres, increasing the strength and toughness of carbon fibers, enhancing the hardness and wear resistance of carbon fibers, and subsequently improving the corresponding properties of PEEK materials.
[0013] Optionally, the mass ratio of the carbon fibers, hollow glass microspheres and nano-silver particles is 1:0.5-0.7:0.1-0.2.
[0014] By adopting the above technical scheme, the mass ratio of carbon fiber, hollow glass microbeads and nanosilver particles is further limited within a certain range, which significantly improves the strength, toughness and wear resistance of carbon fiber. Carbon fiber has the characteristics of high strength, high modulus and low density. Hollow glass microbeads have the characteristics of light weight, high strength, insulation and heat resistance. Nanosilver particles have excellent antibacterial properties. Hollow glass microbeads can be loaded on the surface and pores of carbon fiber. Nanosilver particles can be loaded in the pores of carbon fiber and hollow glass microbeads, which improves the strength and toughness of carbon fiber, enhances the hardness and wear resistance of carbon fiber, and subsequently improves the corresponding properties of PEEK material.
[0015] Optionally, the nanosilver particle pretreatment method comprises the following steps: dispersing the nanosilver particles in an ethanol solution, adding carbon fiber nanosheets and polyvinyl pyrrolidone, heating in a water bath, stirring at a temperature of 60-65° C. for 30-35 minutes, filtering, and drying to obtain pretreated nanosilver particles.
[0016] By adopting the above technical scheme, the nanosilver particles have antibacterial properties and strength, the carbon fiber nanosheets have high modulus and high strength, the nanosilver particles can be loaded on the surface of the carbon fiber nanosheets, thereby improving the tensile strength, wear resistance and impact resistance of the system, and the polyvinyl pyrrolidone has a dispersing effect, thereby making the nanosilver particles and the carbon fiber nanosheets evenly dispersed to prevent their agglomeration, and at the same time making the nanosilver particles evenly dispersed on the surface of the carbon fiber nanosheets, and the nanosilver particles, the carbon fiber nanosheets and the polyvinyl pyrrolidone have a synergistic effect, thereby enhancing the antibacterial properties, strength and wear resistance of the system, and contributing to the subsequent improvement of the corresponding properties of the carbon fiber.
[0017] Optionally, the method for preparing the modified glass fiber comprises the following steps: (1) dispersing glass fibers in an acetone solution, stirring for 2-3 hours, washing with water, and stirring at 220-230° C. for 3-4 hours to obtain pretreated glass fibers; (2) dispersing nano zinc oxide in deionized water, adding hydrochloric acid to adjust the pH value to 5-6, then adding titanate, stirring at 40-45° C. for 1-2 hours, washing, and obtaining modified zinc oxide; (3) dispersing the glass fiber treated in step (1) in deionized water, adding the modified zinc oxide and titanium dioxide in step (2), stirring at a temperature of 80-85° C. for 1-2 hours, filtering to obtain a mixture, spraying chitosan solution on the surface of the mixture, and drying to obtain modified glass fiber.
[0018] By adopting the above technical solution, acetone is used to clean grease, dirt and other organic impurities on the surface of the glass fiber, change the surface properties of the glass fiber, and improve its compatibility and interfacial bonding with the matrix material; heating is further used to remove organic matter on the surface of the glass fiber, change the surface properties of the glass fiber, and improve its surface roughness, which is helpful for the subsequent mixing of the glass fiber with other components.
[0019] Nano zinc oxide has good antibacterial properties, tensile strength, compressive strength and impact resistance. When mixed with titanate, it improves the dispersibility of nano zinc oxide in the matrix material, avoids the agglomeration of nanoparticles, improves the thermal stability of the composite material, and is suitable for applications in high temperature environments.
[0020] Glass fiber, modified zinc oxide and titanium dioxide are mixed. Titanium dioxide has high strength and high toughness. Modified zinc oxide has good antibacterial and mechanical properties. Modified zinc oxide and titanium dioxide can be loaded in the pores and surface of glass fiber to improve mechanical strength and wear resistance such as tensile strength, compressive strength and impact resistance. Moreover, surface treatment of modified zinc oxide and titanium dioxide can improve their dispersibility in the matrix material, avoid agglomeration of nanoparticles, and enhance the interfacial bonding force with glass fiber. Finally, chitosan solution is sprayed on the surface of the mixture to stabilize the connection between glass fiber, modified zinc oxide and titanium dioxide, thereby improving the performance stability of modified glass fiber and subsequently improving the corresponding performance of PEEK material.
[0021] Optionally, the mass ratio of the glass fiber, nano zinc oxide and titanium dioxide is 1:0.3-0.5:0.1-0.2.
[0022] By adopting the above technical scheme, the mass ratio of glass fiber, nano zinc oxide and titanium dioxide is further limited within a certain range, the glass fiber has high strength, high modulus and low density, the nano zinc oxide has good antibacterial properties, tensile strength, compressive strength and impact resistance, titanium dioxide has high strength and high toughness, the mixture of glass fiber, modified zinc oxide and titanium dioxide has a synergistic effect, the modified zinc oxide and titanium dioxide can be loaded on the surface and pores of the glass fiber, and the tensile strength, compressive strength, impact resistance and rigidity of the glass fiber are significantly improved, which is suitable for improving the corresponding properties of PEEK materials.
[0023] Optionally, the method for preparing the chitosan solution comprises the following steps: dispersing chitosan in a citric acid solution with a concentration of 40-50 g / L, adding viscose fiber and nanocellulose, and continuing stirring for 1-2 hours to obtain a chitosan solution.
[0024] By adopting the above technical solution, viscose fiber has good biocompatibility and mechanical properties. When mixed with chitosan, the mechanical strength, toughness, molding performance and biocompatibility of the chitosan system are improved. Nanocellulose has extremely high mechanical strength and rigidity. When combined with chitosan, it can significantly improve the mechanical properties of chitosan, such as tensile strength, modulus and toughness. The mixing of chitosan, viscose fiber and nanocellulose has a synergistic effect, which improves the mechanical strength, toughness and molding performance of the system, helps the coating of glass fiber, makes the glass fiber, nano zinc oxide and titanium dioxide bond tightly, and then improves the corresponding performance of glass fiber.
[0025] Preferably, the compatibilizer is one or a mixture of POE grafted with maleic anhydride with a grafting rate of 0.5-1%, SEBS grafted with maleic anhydride and n-butyl acrylate-glycidyl ester.
[0026] By adopting the above technical solution, the compatibilizer improves the interfacial compatibility between PEEK and polytetrafluoroethylene, reduces the interfacial tension between PEEK and polytetrafluoroethylene, promotes the uniform dispersion of the two, forms a more stable mixed system, and improves the mechanical strength, toughness, impact resistance and wear resistance of PEEK, so that it performs better when subjected to external forces.
[0027] Preferably, the antioxidant is one of antioxidant 9228, antioxidant 608, antioxidant TP-24 and antioxidant 1024, or a mixture of several of them.
[0028] By adopting the above technical solution, the role of the antioxidant in the fan frame is mainly reflected in protecting the material from oxidative degradation and extending the service life of the fan frame.
[0029] In the second aspect, the present application provides a method for preparing a novel PEEK material for a fan frame system, comprising the following steps: evenly mixing PEEK, polytetrafluoroethylene, a compatibilizer, an antioxidant, carbon fiber, and modified glass fiber, melt-extruding at an extrusion temperature of 380-390°C, to obtain a novel PEEK material for a fan frame system.
[0030] By adopting the above technical solution, the preparation method of the present application is simple and suitable for industrial production. The obtained PEEK material has good mechanical strength and durability, which is conducive to the long-term use of the new fan frame.
[0031] In summary, this application has the following beneficial effects: 1. The density of PEEK in this application is relatively low, which realizes the lightweight of the new fan frame. PEEK has high strength, high rigidity and good wear resistance, can withstand the vibration and impact generated during the operation of the fan, maintain the structural stability and integrity of the frame, and help improve the reliability and safety of the fan; PEEK also has excellent chemical resistance and high temperature resistance, can resist the erosion of corrosive substances, and extend the service life of the fan frame.
[0032] 2. The carbon fiber in this application has good corrosion resistance, good thermal stability, extremely high tensile strength and rigidity, is light in weight, and can withstand the high wind pressure and dynamic loads generated when the fan is running, so that the fan frame has high strength. When combined with PEEK, the mechanical properties of the PEEK material such as tensile strength, compressive strength and rigidity are improved. In addition, the hardness and wear resistance of carbon fiber make the PEEK material perform well in friction and wear environments, extending the service life of the material.
[0033] 3. The modified glass fiber in this application has high tensile strength and corrosion resistance, so that the fan can withstand dynamic loads during operation, ensuring the stability and safety of the frame structure. It is combined with PEEK and carbon fiber to improve the wear resistance, tensile strength, compressive strength and corrosion resistance of the PEEK material. Various raw materials cooperate with each other to jointly improve the mechanical strength and wear resistance of the PEEK material. It will be subsequently applied to the new fan frame to improve the durability of the new fan frame and extend the service life of the new fan frame. DETAILED DESCRIPTION
[0034] Preparation example of carbon fiber pretreatment Preparation Example 1-1 Carbon fiber is pretreated, including the following steps: (1) 1.2 kg of carbon fiber was dispersed in 1.5 L of 2.5% hydrogen peroxide, stirred for 20 min, washed with water, and then dispersed in 1.4 L of 65% concentrated nitric acid, stirred at 70 ° C for 1 h, filtered, and rinsed to obtain surface-treated carbon fiber; (2) dispersing the hollow glass microspheres in 1 L of 98% concentrated sulfuric acid, stirring for 20 min, washing with water, and then dispersing them in 0.8 L of 0.8% silane coupling agent aqueous solution, stirring for 2 h, and filtering to obtain pretreated hollow glass microspheres; (3) Dispersing the surface-treated carbon fiber of step (1) in 2 L of deionized water, adding the pretreated hollow glass microbeads and nanosilver particles of step (2), stirring for 2 h, and filtering to obtain pretreated carbon fiber.
[0035] The mass ratio of carbon fiber, hollow glass microspheres and nano-silver particles is 1:0.5:0.1.
[0036] The nano silver particle pretreatment method comprises the following steps: dispersing 0.5 kg of nano silver particles in 1 L of ethanol solution, adding 0.1 kg of carbon fiber nano sheets and 0.02 kg of polyvinyl pyrrolidone, heating in a water bath, stirring at a temperature of 60-65° C. for 30-35 minutes, filtering, and drying to obtain pretreated nano silver particles.
[0037] Preparation Example 1-2 The difference from Preparation Example 1-1 is that in step (2), no hollow glass microspheres are added.
[0038] Preparation Example 1-3 The difference from Preparation Example 1-1 is that in step (3), no nanosilver particles are added.
[0039] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of carbon fiber, hollow glass microspheres and nano-silver particles is 1:0.7:0.2.
[0040] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of carbon fiber, hollow glass microspheres and nano-silver particles is 1:0.1:0.5.
[0041] Preparation Example 1-6 The difference from Preparation Example 1-1 is that no carbon fiber nanosheets are added in the nanosilver particle pretreatment method.
[0042] Preparation Example 1-7 The difference from Preparation Example 1-1 is that polyvinyl pyrrolidone is not added in the nanosilver particle pretreatment method.
[0043] Preparation example of modified glass fiber Preparation Example 2-1 The preparation method of modified glass fiber comprises the following steps: (1) 1.0 kg of glass fiber was dispersed in 1.5 L of acetone solution, stirred for 3 h, washed with water, and stirred at 220 ° C for 3 h to obtain pretreated glass fiber; (2) dispersing nano zinc oxide in 0.9 L of deionized water, adding hydrochloric acid to adjust the pH value to 5, then adding titanate coupling agent ZJ-311, stirring at 40° C. for 1.5 h, washing, and obtaining modified zinc oxide; (3) Dispersing the glass fiber treated in step (1) in 2 L of deionized water, adding the modified zinc oxide and titanium dioxide in step (2), stirring at a temperature of 85° C. for 2 h, filtering to obtain a mixture, spraying 0.2 kg of chitosan solution on the surface of the mixture, and drying to obtain modified glass fiber.
[0044] The mass ratio of glass fiber, nano zinc oxide and titanium dioxide is 1:0.3:0.2.
[0045] The preparation method of chitosan solution comprises the following steps: dispersing 0.3 kg chitosan in 1 L citric acid solution with a concentration of 45 g / L, adding 0.1 kg viscose fiber and 0.05 kg nanocellulose, and continuing stirring for 1.5 hours to obtain chitosan solution.
[0046] Preparation Example 2-2 The difference from Preparation Example 2-1 is that in step (2), no nano zinc oxide is added.
[0047] Preparation Example 2-3 The difference from Preparation Example 2-1 is that in step (3), titanium dioxide is not added.
[0048] Preparation Example 2-4 The difference from Preparation Example 2-1 is that in step (3), the chitosan solution is not sprayed.
[0049] Preparation Example 2-5 The difference from Preparation Example 2-1 is that the mass ratio of glass fiber, nano zinc oxide and titanium dioxide is 1:0.5:0.1.
[0050] Preparation Example 2-6 The difference from Preparation Example 2-1 is that the mass ratio of glass fiber, nano zinc oxide and titanium dioxide is 1:0.1:0.6.
[0051] Preparation Example 2-7 The difference from Preparation Example 2-1 is that no viscose fiber is added in the preparation method of the chitosan solution.
[0052] Preparation Example 2-8 The difference from Preparation Example 2-1 is that nanocellulose is not added in the preparation method of the chitosan solution. Example
[0053] Example 1 A new type of PEEK material for a fan frame system includes the following raw materials: by weight, the raw materials include: 55kg of PEEK, 12kg of polytetrafluoroethylene, 2kg of a compatibilizer, 1kg of an antioxidant, 15kg of carbon fiber, and 7kg of modified glass fiber.
[0054] The compatibilizer is PTW from DuPont of the United States, and the antioxidant is antioxidant 9228.
[0055] The preparation method of a novel PEEK material for a fan frame system comprises the following steps: uniformly mixing PEEK, polytetrafluoroethylene, a compatibilizer, an antioxidant, carbon fiber and modified glass fiber, and melt-extruding the mixture at a temperature of 390° C. to obtain a novel PEEK material for a fan frame system.
[0056] The carbon fiber pretreatment was prepared by using Preparation Example 1-1, and the modified glass fiber was prepared by using Preparation Example 2-1.
[0057] Example 2 A novel PEEK material is used for manufacturing a fan frame. The difference from Example 1 is that the novel PEEK material includes the following raw materials: 60 kg of PEEK, 9 kg of polytetrafluoroethylene, 5 kg of compatibilizer, 2 kg of antioxidant, 20 kg of carbon fiber, and 10 kg of modified glass fiber.
[0058] Example 3 A novel PEEK material is provided for fan frame manufacturing. The difference from Example 1 is that the carbon fiber pretreatment is prepared by using Preparation Example 1-2.
[0059] Example 4 A novel PEEK material is provided for fan frame manufacturing. The difference from Example 1 is that the carbon fiber pretreatment is prepared by using Preparation Example 1-3.
[0060] Example 5 A novel PEEK material is provided for fan frame manufacturing. The difference from Example 1 is that the carbon fiber pretreatment is prepared by using Preparation Examples 1-4.
[0061] Example 6 A novel PEEK material is provided for fan frame manufacturing. The difference from Example 1 is that the carbon fiber pretreatment is prepared by using Preparation Example 1-5.
[0062] Example 7 A novel PEEK material is provided for fan frame manufacturing. The difference from Example 1 is that the carbon fiber pretreatment is prepared by using Preparation Examples 1-6.
[0063] Example 8 A novel PEEK material is provided for fan frame manufacturing. The difference from Example 1 is that the carbon fiber pretreatment is prepared by using Preparation Example 1-7.
[0064] Example 9 A novel fan frame is made of PEEK material. The difference from Example 1 is that the modified glass fiber is prepared by Preparation Example 2-2.
[0065] Example 10 A novel fan frame is made of PEEK material, which is different from Example 1 in that the modified glass fiber is prepared using Preparation Example 2-3.
[0066] Embodiment 11 A novel PEEK material is used for a fan frame. The difference from Example 1 is that the modified glass fiber is prepared using Preparation Example 2-4.
[0067] Example 12 A novel fan frame is made of PEEK material, which is different from Example 1 in that the modified glass fiber is prepared using Preparation Example 2-5.
[0068] Embodiment 13 A novel PEEK material is provided for fan frame, which is different from Example 1 in that the modified glass fiber is prepared by using Preparation Example 2-6.
[0069] Embodiment 14 A novel PEEK material is provided for fan frame, which is different from Example 1 in that the modified glass fiber is prepared by Preparation Example 2-7.
[0070] Embodiment 15 A novel PEEK material is used for a fan frame. The difference from Example 1 is that the modified glass fiber is prepared using Preparation Example 2-8.
[0071] Comparative Example Comparative Example 1 A novel fan frame is made of PEEK material, which is different from Example 1 in that no carbon fiber is added.
[0072] Comparative Example 2 A novel fan frame is made of PEEK material, which differs from Example 1 in that modified glass fiber is not added.
[0073] Comparative Example 3 A novel fan frame is made of PEEK material, which differs from Example 1 in that glass fiber is used instead of an equal amount of modified glass fiber.
[0074] Performance testing The performance of the novel fan frame prepared in Examples 1-15 and Comparative Examples 1-3 was tested using PEEK materials; The tests of tensile strength, bending strength and compressive strength are carried out according to GB1040-79, GB1041-79 and GB1042-79; the friction and wear test conditions are: initial load 196N, rotation speed 200r / min, dry friction 2h, grinding wheel: 45 steel, 42-45HRC, the test results are shown in Table 1.
[0075] Table 1 Test data of embodiments and comparative examples Combining the examples and the data in the table, it can be seen that the novel PEEK materials for wind turbine frame systems prepared in Examples 1-2, Example 5, and Example 12 have good mechanical properties, mechanical strength, and wear resistance. Among them, the tensile strength of Example 1 is 108 MPa, the bending strength is 175 MPa, the compressive strength is 138 MPa, the friction coefficient is 0.10, and the wear rate is 1.26×10 - 7 mm 3 / Nm, indicating that various raw materials cooperate with each other to jointly improve the mechanical strength and wear resistance of PEEK materials, which will be subsequently applied to new fan frames to improve the durability of new fan frames and extend the service life of new fan frames.
[0076] In the carbon fiber pretreatment of Example 3, hollow glass microspheres are not added. As shown in Table 1, compared with Example 1, the tensile strength is 97 MPa, the bending strength is 162 MPa, the compressive strength is 124 MPa, the friction coefficient is 0.23, and the wear rate is 1.41×10-7 mm 3 / Nm, indicating that hollow glass microspheres have the characteristics of light weight, high strength, insulation, and heat resistance, which can improve the strength, toughness, and wear resistance of carbon fibers, thereby improving the corresponding properties of PEEK materials.
[0077] In the carbon fiber pretreatment of Example 4, nanosilver particles are not added. As shown in Table 1, compared with Example 1, the tensile strength is 92 MPa, the bending strength is 157 MPa, the compressive strength is 118 MPa, the friction coefficient is 0.29, and the wear rate is 1.46×10 - 7 mm 3 / Nm, indicating that nanosilver particles can be loaded in the pores of carbon fibers and hollow glass microspheres, improving the strength and toughness of carbon fibers, enhancing the hardness and wear resistance of carbon fibers, and subsequently improving the corresponding properties of PEEK materials.
[0078] Example 6 changes the mass ratio of carbon fiber, hollow glass microspheres and nanosilver particles. As can be seen from Table 1, the tensile strength, flexural strength, compressive strength and wear resistance are better than those of Examples 3-4, but worse than those of Examples 1-2 and Example 5, indicating that the hollow glass microspheres can be loaded on the surface and pores of the carbon fiber, and the nanosilver particles can be loaded in the pores of the carbon fiber and the hollow glass microspheres, thereby improving the strength and toughness of the carbon fiber, enhancing the hardness and wear resistance of the carbon fiber, and subsequently improving the corresponding properties of the PEEK material.
[0079] In the nanosilver particle pretreatment method of Examples 7-8, carbon fiber nanosheets and polyvinyl pyrrolidone are not added respectively. As can be seen from Table 1, the tensile strength, flexural strength, compressive strength and wear resistance are worse than those of Example 4, indicating that the nanosilver particles can be loaded on the surface of the carbon fiber nanosheets, thereby improving the tensile strength, wear resistance and impact resistance of the system. Polyvinyl pyrrolidone has a dispersing effect, which makes the nanosilver particles and carbon fiber nanosheets evenly dispersed, thereby enhancing the antibacterial properties, strength and wear resistance of the system, and contributing to the subsequent improvement of the corresponding properties of the carbon fiber.
[0080] In Example 9, nano zinc oxide is not added to the modified glass fiber. As shown in Table 1, compared with Example 1, the tensile strength is 99 MPa, the bending strength is 164 MPa, the compressive strength is 126 MPa, the friction coefficient is 0.20, and the wear rate is 1.38×10 - 7 mm 3 / Nm, indicating that nano zinc oxide has good antibacterial properties, tensile strength, compressive strength and impact resistance. The mechanical strength and wear resistance of PEEK materials such as tensile strength, compressive strength and impact resistance are subsequently improved. Titanium dioxide is not added to the modified glass fiber in Example 10. As can be seen from Table 1, compared with Example 1, the tensile strength is 97MPa, the bending strength is 160MPa, the compressive strength is 122MPa, the friction coefficient is 0.25, and the wear rate is 1.43×10 -7 mm 3 / Nm, indicating that titanium dioxide has high strength and high toughness. Titanium dioxide can be loaded in the pores and surface of glass fibers to improve mechanical strength and wear resistance such as tensile strength, compressive strength and impact resistance.
[0081] In Example 11, chitosan solution is not sprayed in the modified glass fiber. As shown in Table 1, compared with Example 1, the tensile strength is 94 MPa, the bending strength is 158 MPa, the compressive strength is 120 MPa, the friction coefficient is 0.26, and the wear rate is 1.42×10 - 7 mm 3 / Nm, indicating that the chitosan solution helps to coat the glass fiber, making the glass fiber, nano-zinc oxide and titanium dioxide bond tightly, thereby improving the corresponding properties of the glass fiber.
[0082] Example 13 changes the mass ratio of glass fiber, nano zinc oxide and titanium dioxide. It can be seen from Table 1 that the tensile strength, flexural strength, compressive strength and wear resistance are better than those of Examples 9-10, but worse than those of Examples 1-2 and Example 12, indicating that the mixture of glass fiber, modified zinc oxide and titanium dioxide has a synergistic effect, and the modified zinc oxide and titanium dioxide can be loaded on the surface and pores of the glass fiber, significantly improving the tensile strength, compressive strength, impact resistance and rigidity of the glass fiber, and is suitable for improving the corresponding properties of PEEK material.
[0083] In the preparation methods of the chitosan solutions of Examples 14-15, viscose fiber and nanocellulose are not added respectively. As can be seen from Table 1, the tensile strength, flexural strength, compressive strength and wear resistance are worse than those of Example 11, indicating that the mixing of chitosan, viscose fiber and nanocellulose has a synergistic effect, which improves the mechanical strength, toughness and molding properties of the system, helps to coat the glass fiber, makes the glass fiber, nano zinc oxide and titanium dioxide bond tightly, and thus improves the corresponding properties of the glass fiber.
[0084] In Comparative Example 1, no carbon fiber is added. As shown in Table 1, compared with Example 1, the tensile strength is 78 MPa, the bending strength is 145 MPa, the compressive strength is 103 MPa, the friction coefficient is 0.73, and the wear rate is 2.04×10 -7 mm3 / Nm, indicating that carbon fiber has good corrosion resistance, thermal stability, extremely high tensile strength and wear resistance, and can withstand the high wind pressure and dynamic load generated when the fan is running, making the fan frame have high strength. When combined with PEEK, it improves the mechanical properties of PEEK material such as tensile strength, compressive strength and wear resistance.
[0085] In Comparative Example 2, no modified glass fiber is added. As shown in Table 1, compared with Example 1, the tensile strength is 80 MPa, the bending strength is 148 MPa, the compressive strength is 106 MPa, the friction coefficient is 0.69, and the wear rate is 1.98×10 -7 mm 3 / Nm, indicating that the modified glass fiber has higher tensile strength, corrosion resistance and lower density. It can be combined with PEEK and carbon fiber to improve the wear resistance, tensile strength, compressive strength and corrosion resistance of PEEK materials. In Comparative Example 3, glass fiber is used to replace an equal amount of modified glass fiber. As can be seen from Table 1, the tensile strength, flexural strength, compressive strength and wear resistance are worse than those in Example 1, but better than those in Comparative Examples 1-2, indicating that the modified glass fiber of the present application has higher tensile strength, corrosion resistance and wear resistance, thereby improving the mechanical strength and wear resistance of the PEEK material.
[0086] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A new type of fan frame made of PEEK material, characterized in that: The raw materials are as follows, calculated by weight: 55-60 parts of PEEK, 9-12 parts of polytetrafluoroethylene, 2-5 parts of a compatibilizer, 1-2 parts of an antioxidant, 15-20 parts of carbon fiber, and 7-10 parts of modified glass fiber.
2. The novel fan frame according to claim 1 is made of PEEK material, characterized in that: The carbon fiber is pretreated, comprising the following steps: (1) Dispersing carbon fiber in hydrogen peroxide, stirring for 15-20 minutes, washing with water, and then dispersing in concentrated nitric acid, stirring at a temperature of 66-70°C for 0.5-1h, filtering, and washing to obtain surface-treated carbon fiber; (2) dispersing the hollow glass microspheres in concentrated sulfuric acid, stirring for 20-25 minutes, washing with water, and then dispersing them in an aqueous solution of a silane coupling agent, stirring for 1-2 hours, and filtering to obtain pretreated hollow glass microspheres; (3) Dispersing the surface-treated carbon fiber of step (1) in deionized water, adding the pretreated hollow glass microbeads and nano-silver particles of step (2), stirring for 2-3 hours, and filtering to obtain pretreated carbon fiber.
3. The novel fan frame according to claim 2 is made of PEEK material, characterized in that: The mass ratio of the carbon fiber, the hollow glass microbeads and the nano-silver particles is 1:0.5-0.7:0.1-0.
2.
4. The novel fan frame according to claim 2 is made of PEEK material, characterized in that: The nano silver particle pretreatment method comprises the following steps: dispersing the nano silver particles in an ethanol solution, adding carbon fiber nano sheets and polyvinyl pyrrolidone, heating in a water bath, stirring at a temperature of 60-65° C. for 30-35 minutes, filtering, and drying to obtain pretreated nano silver particles.
5. The novel fan frame according to claim 1 is made of PEEK material, characterized in that: The preparation method of the modified glass fiber comprises the following steps: (1) dispersing the glass fiber in an acetone solution, stirring for 2-3 hours, washing with water, and stirring at 220-230° C. for 3-4 hours to obtain pretreated glass fiber; (2) dispersing nano zinc oxide in deionized water, adding hydrochloric acid to adjust the pH value to 5-6, then adding titanate, stirring at 40-45°C for 1-2h, washing, and obtaining modified zinc oxide; (3) Dispersing the glass fiber treated in step (1) in deionized water, adding the modified zinc oxide and titanium dioxide in step (2), stirring at a temperature of 80-85° C. for 1-2 hours, filtering to obtain a mixture, spraying chitosan solution on the surface of the mixture, and drying to obtain modified glass fiber.
6. The novel fan frame according to claim 5 is made of PEEK material, characterized in that: The mass ratio of the glass fiber, nano zinc oxide and titanium dioxide is 1:0.3-0.5:0.1-0.
2.
7. The novel fan frame according to claim 5 is made of PEEK material, characterized in that: The method for preparing the chitosan solution comprises the following steps: dispersing chitosan in a citric acid solution with a concentration of 40-50 g / L, adding viscose fiber and nanocellulose, and continuing stirring for 1-2 hours to obtain the chitosan solution.
8. The novel fan frame according to claim 1 is made of PEEK material, characterized in that: The compatibilizer is one or a mixture of POE grafted maleic anhydride with a grafting rate of 0.5-1%, SEBS grafted maleic anhydride and n-butyl acrylate-glycidyl ester.
9. The novel fan frame according to claim 1 is made of PEEK material, characterized in that: The antioxidant is one of antioxidant 9228, antioxidant 608, antioxidant TP-24 and antioxidant 1024 or a mixture of several of them.
10. The method for preparing a novel PEEK material for a fan frame according to claim 1, characterized in that: The method comprises the following steps: uniformly mixing PEEK, polytetrafluoroethylene, a compatibilizer, an antioxidant, carbon fiber and modified glass fiber, and melt-extruding the mixture at a temperature of 380-390 DEG C to obtain a novel PEEK material for a fan frame system.